APPLYING POSITIVE REINFORCEMENT TO INCREASE STUDENTS’ MOTIVATION IN LEARNING ENGLISH FOR GRADE VII IN SMP PANGUDI LUHUR 1 YOGYAKARTA - Emmelia Dyah; Patricia Angelina (ELTR Journal, 2018)
This research aims to find out how the positive reinforcement is given to motivate the seventh grade students in SMP Pangudi Luhur 1 Yogyakarta and to explain the benefits of applying positive reinforcement. In order to answer the two research problems; how is positive reinforcement given to motivate the students in SMP Pangudi Luhur 1 Yogyakarta and what are the benefits of applying positive reinforcement in SMP Pangudi Luhur 1 Yogyakarta, the researcher used mixed-method for this research. The researcher used three theories in order to answer the first and second research problems. For the first problem, the researcher used the theory from Becker, Engelman, and Thomas (1975) which explained about the ways of apply positive reinforcement.Meanwhile, the theories from Al-Tamimi and Shuib (2009) and Maehr (1984) which defined about the benefits of applying positive reinforcement were used to answer the second research problem. Those threetheories used as the foundation in making observation checklist and questionnaire. The researcher applied Classroom Action Research (CAR) for this research. The research showed that applying positive reinforcement in the form of giving praise and extra score was used by English tutor to motivate the students in learning English.